Genetic Polymorphisms in CD35 Gene Contribute to the Susceptibility and Prognosis of Hepatocellular Carcinoma - Luo, Limei; Li, Qin; Su, Zhenzhen; Li, Lixin; Cai, Bei; Peng, Yufu; Bai, Yangjuan; Liu, Fei (Frontiers in Oncology, 2021)
CD35, an important molecule implicated in inflammation and immunity, is reportedly associated with several cancers. However, very few studies have investigated the relationship between CD35 polymorphisms and hepatocellular carcinoma (HCC). The current study was conducted to investigate the association between tag SNPs in CD35 and HCC susceptibility and postoperative recurrence, in an attempt to elucidate the gene-environment interactions in HCC. A total of 1233 Chinese Han people, including 647 healthy controls and 586 HCC cases, were sampled in this study. Six Tag SNPs (rs10494885, rs2296160, rs3737002, rs3849266, rs669117, and rs7525160) of CD35 were selected using the HaploView 4.2 program and genotyped by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS). Overall, the mutation genotypes CC/CG of CD35 rs7525160 significantly increased the risk of HCC. Stratification analysis indicated that CD35 rs7525160 CC/CG genotypes increased HCC risk in patients younger than 65 years and were closely related to the pathological type of poor prognosis of HCC. Cox proportional hazard ratio model analysis revealed that the rs7525160 CC/CG genotype remains a significant independent risk factor for postoperative recurrence of HCC. In conclusion, CD35 rs7525160 polymorphism may contribute to the susceptibility and prognosis of HCC in the Chinese Han population.